Comparison of the level of dynamic postural stability of climbers and the recreational sports performing population - Karšayová, K.; Pavlu, D.; Vomácková, H. (International Journal of Applied Exercise Physiology, 2020)
During climbing, the climber is exposed to a constant risk of falling as a result of the force of gravity. The correct anticipatory postural adjustment of the body is also required for a good climbing movement. Posture and movement are interconnected and provide posture-kinetic coordination of the body, which consists in the inseparability of biomechanical and sensory attributes of a movement [1, 2]. In the field of climbing, most authors deal with biomechanical aspects of the posture during individual stages of climbing movement. The aim of this research is to focus more on the sensory component. A total of 40 subjects participated in the measurement of dynamic postural stability using instrumentation from Neurocom International Inc. The applied tests were the Limits of stability test (LOS), Sensory organization test (SOT) and Motor control test (MCT). Then, statistical processing of data and subsequent evaluation and comparison of both groups of subjects (climbers x non-climbers) were performed. SOT -a statistically significant difference was found in COND6 (standingwith open eyes and an unstable support and environment), mainly due to the somatosensory system. The p-value was 0.04 in this case. LOS -DC (directional control) parameter -a statistically significant difference of values was found, where the p-value was 0.04. Climbers had statistically worse directional control than non-climbers in this case. MCT -a statistically significant difference was found in one parameter only. In the case of forward shift at a medium speed (ML -medium shift forward, left), there was a statistically significantly faster response of the left body part of climbers, with a p-value of 0.01. No statistically significant data were found in the other variables. Based on statistical data processing, we cannot claim that climbers achieved statistically significantly better results in the selected parameters than non-climbers. However, when comparing arithmetic means, the group of climbers was confirmed to be better in 17 out of 27 of the tested parameters (63%); therefore, our research suggests a certain tendency that climbing has a positive effect on dynamic postural stability. Therefore, in the future it would be useful to deal with this topic further with more specific measurements.